Rancang Bangun Aplikasi Pengontrolan Kupon BBM Kendaraan Dinas Dan Pelaporan Konsumsinya Dengan Sms Gateway Berbasis Barcode - Tadjuka, M A; Jaya, A I; Ratianingsih, R (Program Studi Matematika, Universitas Tadulako, 2019)
ABSTRACTThis study offers design of SMS Gateway application based a barcode- SMS Gateway for controlling theconsumption of fuel and reporting the consumption of official vehicles of Tadulako University, Department ofHygiene of Palu City and POLSEK of Easten Palu City. Barcode is an encoded information in form of thin and wide stripe with white line spacing in between. Controlling the fuel consumption is done by recapitulation the data that is send by SMS. It is contain information about the rest of quota for the current month. This application use open source softwares such us Gammu, MySql, Xampp, and PHP. The resulting application only transmit direct current month quota to the institution of Tadulako University, Department of Hygiene of Palu City and POLSEK of Easten Palu City.Keywords : Barcode, Gammu, MySql, PHP, SMS Gateway, Xampp.